Smart Resources in Ophthalmology Applications and Social Networking - Ichhpujani, Parul (Current Practices in Ophthalmology,, 2018)
This book provides information on how to extract the most from mobile applications and easily adapt and integrate them into daily practice. Today mobile applications that can optimize patient flow, help in examinations, perform anterior/posterior segment imaging, offer differential diagnosis and therapeutic options and even serve as patient drug reminders and councilors are easily available. Most of them have been developed by individuals and as a result lack marketing, even though they are free to download and use. Ophthalmology has always been at the forefront of medicine when it comes to adopting the latest developments - be they lasers, off-label anti-VEGF drugs or biocompatible implants. Mobile phones and tablets have infiltrated our private and professional lives and they are here to stay. As such, this book explores the endless possibilities that mobile computing offers, and introduces the vista of opportunities for providing better care, one download at a time. As part of the series "Current Practices in Ophthalmology" this volume is intended for residents and fellows in-training, as well as general and specialist ophthalmologists.